Structural, magnetic, dielectric and magneto-dielectric properties of (BaTiO3)0.70(Li0.3Zn0.4Fe2.3O4)0.30. (June 2018) - Mahapatra, A.S.; Mitra, A.; Mallick, A.; Shaw, A.; Chakrabarti, P.K.
Graphical abstract: Highlights: Microcrystals of BaTiO3 is incorporated in Li0.3 Zn0.4 Fe2.3 O4 using sol-gel method. Crystallographic phase and morphology of the composite is investigated. Magnetic ordering originates from the ferrimagnetic matrix of the composite. The dielectric behaviour is originated from the BaTiO3 particles in the composite. The composite shows strong magneto-electric property, useful for application. Abstract: Structural, magnetic, dielectric and magneto-dielectric properties of (BaTiO3 )0.70 (Li0.3 Zn0.4 Fe2.3 O4 )0.30 [BTO-LZFO] composite are studied. To prepare the composite, microcrystals of BaTiO3 [BTO] prepared in solid-state reaction are taken along with the precursors of Li0.3 Zn0.4 Fe2.3 O4 [LZFO], prepared in sol-gel route. X-ray diffraction (XRD) study confirms the phase purity of the composite sample. High-resolution transmission electron microscopy also confirms the formation of the composite state. Analysis of magnetic data confirms the ferrimagnetic nature of the sample along with a fraction of superparamagnetic particles. The ferrimagnetism is explained by Néels' two-sublattice model. The dielectric spectrum of the sample follows the Cole-Cole relaxation. Interestingly, the ferroelectric and dielectric behaviours of BTO are retained in the composite state of BTO-LZFO, though the magnetization is enhanced drastically. This enhanced magnetic property along with the ferroelectricity and strong magneto-dielectric coupling in the composite state confirms that BTO-LZFO can be used as a multiferroic material in different electronic devices.